2010
DOI: 10.1002/jmr.1002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the disorder–order transition of calmodulin binding domain upon binding calmodulin using molecular dynamics simulation

Abstract: We have studied the conformational transition of the calmodulin binding domains (CBD) in several calmodulin-binding kinases, in which CBD changes from the disordered state to the ordered state when binding with calmodulin (CaM). Targeted molecular dynamics simulation was used to investigate the binding process of CaM and CBD of CaM-dependent kinase I (CaMKI-CBD). The results show that CaMKI-CBD began to form an alpha-helix and the interaction free energy between CaM and CaMKI-CBD increased once CaM fully encom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…In this study, we implemented a "staircase" variation of tMD (stMD) (39) in which RMSD target (t) is reduced from RMSD(0) in "staircases", i.e. alternating steps of targeted motion ("move") and constrained equilibration ("pause"); this procedure allowed us to compute averages along transition "pauses" of constant RMSD target (t) values.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we implemented a "staircase" variation of tMD (stMD) (39) in which RMSD target (t) is reduced from RMSD(0) in "staircases", i.e. alternating steps of targeted motion ("move") and constrained equilibration ("pause"); this procedure allowed us to compute averages along transition "pauses" of constant RMSD target (t) values.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the flexibility of the interdomain linker is essential to the rearrangement of the two domains of CaM in order to accommodate binding of a wide selection of targets (Wriggers et al ., ; Ikura and Ames, ). Simulation and theoretical studies have suggested that in addition to the conformational flexibility of CaM (Vigil et al ., ; Barton et al ., ; Chen and Luo, ; Tripathi and Portman, ), both the hydrophobic and electrostatic interactions are important in CaM–target binding (Yang et al ., ; Fiorin et al ., ; Zhang et al ., ; Smith Dayle et al ., ). Nevertheless, the molecular basis of the binding mechanism that enables CaM to recognize highly diverse target proteins remains elusive.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrophobic residues of the CaMBTs from the hydrophobic motifs (1-5-10 and 1-14 for CaMKI and 1-5-10 for CaMKII) in both the sequences are colored in red. Tripathi and Portman, 2009), both the hydrophobic and electrostatic interactions are important in CaM-target binding (Yang et al, 2004;Fiorin et al, 2006;Zhang et al, 2009;Smith Dayle et al, 2012). Nevertheless, the molecular basis of the binding mechanism that enables CaM to recognize highly diverse target proteins remains elusive.…”
Section: Cam and Cambtsmentioning
confidence: 99%
“…Due to the importance of CaM in the Ca 2+ signals pathway, it has been the focus of extensive studies in the past several decades, including many versions of its X-ray or NMR structures [9], [10], [11], [12], its metal-binding properties [4], [13], [14], the interaction with its target proteins [7], [15], and its stability and dynamics in water environment and so on. Of interest, several published papers are related with the folding/unfolding properties of CaM [16], [17], [18], [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%